Banking on indigenous communities issues, options and Australian and international best practice - McDonnell, Siobhan; Westbury, N. (Neil); Australian National University. Centre for Aboriginal Economic Policy Research ([Canberra] : Centre for Aboriginal Economic Policy Research, 2002)
The ability of people to manage and budget their incomes, arrange to pay third parties, purchase food, goods and services, and maintain a level of financial and economic independence and planning, all rely on maintaining informed access to appropriate banking and financial services. The rhetoric of economic independence is commonly employed as a laudable objective for Indigenous peoples. However, there is little evidence of systematic attention being applied to ensuring Indigenous Australians can even enjoy equitable levels of access to those essential banking and financial services that are taken for granted by other Australians (Reconciliation Australia Strategic Plan 2001-2003).
Includes bibliographical references.
Title from title screen (viewed on June 4, 2003).
Text.
Mode of access: Internet via World Wide Web. Address as at 18/07/2011: http://caepr.anu.edu.au/Publications/WP/2002WP18.php.
System requirements: Adobe Acrobat reader required to view title.
Selected for archiving
Keywords: Aboriginal Australians -- Finance; Banks and banking -- Australia; Financial services industry -- Australia; Economic sectors - Financial services; Socioeconomic conditions; Brewarrina (N NSW SH55-06); Goodooga (N NSW SH55-07); Murdi Paaki / Bourke (N NSW SH55-10); Walgett (N NSW SH55-11); Wilcannia (NW NSW SH54-16)